Microbiology of Healthcare-Associated Infections: Results of a Fourth National Point Prevalence Survey in Serbia - Ivana Ćirković; Ljiljana Marković-Denić; Milica Bajčetić; Gorana Dragovac; Zorana Đorđević; Vesna Mioljević; Danijela Urošević; Vladimir Nikolić; Aleksa Despotović; Gordana Krtinić; Violeta Rakić; Ivana Janićijević; et al. (MDPI AG, 2022)
Millions of patients acquire healthcare-associated infections (HAIs) every year, putting them at risk for serious complications and prolonged hospitalization. Point prevalence surveys (PPS), guided by the European Centre for Disease Prevention and Control framework, are one of the primary methods by which countries in the European Union conduct surveillance of HAIs. Serbia, though not in the EU, implemented this approach in its national PPS. The microbiological and antimicrobial resistance (AMR) analyses comprised patients in 61 out of 65 hospitals included in the fourth PPS conducted in November 2017. A total of 515/12,380 (4.2%) of the adult patients included in the PPS had at least one HAI, with intensive care units carrying the highest prevalence of 15.9%. Urinary tract and surgical site infections were the most frequently identified types of HAIs (23.9% and 23.0%, respectively). Enterobacterales comprised almost half (47.0%) of all causative agents, most notably Klebsiella spp. (16.7%). AMR was very high for most pathogens-80.5% of nonfermentative Gram-negative bacilli were resistant to carbapenems whereas 62.9% of Enterobacterales were resistant to third generation cephalosporins. The calculated AMR index of 61% is one of the highest in Europe. Further efforts are needed to reduce the burden of HAIs in Serbia that carry very high resistance rates to antibiotics currently used in clinical practice.